Gap formation after single lateral row versus dual-row suture bridge cuff repair : an ovine biomechanical model - Tan, Kelvin Guoping (2021)
Background: The aim of this study is to compare two types of suture bridging constructs; a laterally based bridging single row (SR) construct and a classic dual row (DR) suture bridge construct. The hypothesis is that the DR construct will demonstrate superior biomechanical properties. Methods: Six matched pairs of sheep infraspinatus tendon tears repaired with these two different types of suture bridging techniques were tested for gap formation, ultimate failure load and mode of failure. The specimens were pre-cycled for 10 cycles before they were subjected to a constant pre-load of 10N. The specimens were then subjected to cyclic loading at a speed of 8.33 mm/s. The test was stopped after every 500 cycles for a total of 3000 cycles. Results: Mean gap formation after 3000 cycles was lower in the DR group (0.81 ± 0.2 mm versus 2.44 ± 0.27 mm; p = 0.002). Mean change in gap (with every 500 cycles) was also lesser for the DR group after 1500 cycles. DR repairs failed at a higher load (523.4 ± 80.4 N) compared to the SR repairs (452.3 ± 66.3 N) but this did not reach significance. All repairs failed with sutures pulling through the tendon during load to failure testing. Conclusions: Gap formation is significantly lower with a dual row suture bridge construct than a laterally based bridging single row construct. Level of evidence: Biomechanical study.